Simplify assume Y=not to 0

(3y^-3)^4

would the answer be 1/81y^12

2 answers

Nope, missed it again.

3^4 * y^(-3)^4 = 81 * y^-12 = 81/y^12

The negative power applies only to y, not the 3 as well.
On the other hand, ((3y)^-3)^4 is 1/(81y^12)
Similar Questions
  1. 1)Simplify:(6x^3-16x^2+11x-5)/(3x-2)answer= 2x^2-4x+1-3over3x-2 2)Factor 27x^3-1 completley. answer= (3x-1)^3 if this isnt
    1. answers icon 0 answers
  2. Find the length of the 3rd side of each right triangle.1. 8^2+15^2=c^2 Answer: c=17 2. 5^2+b^2=13^2 Answer: b=12 3. 9^2+13^2=c^2
    1. answers icon 5 answers
  3. simplifying square roots1) find volume of this prism? v=bwh b=√12" w=√6" h=√8" 2)simplify: √576 3)simplify: √400
    1. answers icon 3 answers
    1. answers icon 1 answer
more similar questions